PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL MASA PANDEMI COVID-19 TERHADAP KEPUASAN KERJA PEGAWAI DI SAMSAT MEDAN SELATAN - Juliyanti, Nur Azizah; Lubis, Anggia Sari (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2021)
The purpose of the study was to determine and analyze the Effect of the Covid-19 Transformational Leadership Style on Employee Job Satisfaction at the South Medan Samsat. Data research design, descriptive and quantitative. The population in this study is the total number of employees at the South Medan Samsat in 2021, amounting to 61 people. The sources of data in this study are primary data and secondary data. Where the primary data from observations, interviews and questionnaires. The data analysis technique used is descriptive analysis and simple linear regression. The results of simple regression analysis are Y=2,062+1,188X+e which shows that transformational leadership style has a positive and significant effect on employee satisfaction. while the results of the (t) test or partial test show that transformational leadership has a positive and significant effect. Regarding employee job satisfaction, it can be seen that the value of tcount =(24,458) > ttable (0,045). Then the coefficient of determination (R2) is 0.955 (95.5%). So it can be said that the variation of the dependent variable, namely transformational leadership in the model, can explain the variable job satisfaction of employees at Samsat Medan Selatan, while the remaining 0.045% is influenced by other variables outside the model.